UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN MANGGA KASTURI (Mangifera casturi Kosterm.) - Lestari, Dwi; MA, Muthia Dwi; Pratiwi, Jati; Saputri, Lidya Handoko (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2021)
Mangga Kasturi (Mangifera casturi Kosterm.) is one of the plants in Indonesia that has potential as an antioxidant. The purpose of this study was to determine the IC50 value and antioxidant potential of the ethanol extract of mangga kasturi leaves (Mangifera casturi Kosterm.). The ethanol extract of mangga kasturi leaves (Mangifera casturi Kosterm.) was extracted using maceration with 96% ethanol as solvent. The antioxidant activity test was carried out using the DPPH (1,1-Diphenyl-2-Picrylhydrazil) method using a UV-Vis spectrophotometer and vitamin C as a comparison. The results of phytochemical screening tests on ethanol extracts showed positive secondary metabolites such as alkaloids, flavonoids, tannins, and quinones. Testing the ethanol extract of Mangga Kasturi leaves (Mangifera casturi Kosterm.) with the DPPH method showed that the ethanol extract had an antioxidant activity with an IC50 value of 83.61 ppm in the strong category of antioxidant potential.